2017
DOI: 10.18805/ijare.a-4714
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weather on grain yield of direct seeded upland rice varieties in Jharkhand, India

Abstract: The study was conducted at Birsa Agricultural University, Ranchi during the years 2009-2013 for understanding the effect of weather variables on the yield of three direct seeded upland rainfed rice varieties viz., Vandana, BVD-109 and BVD-111 in Jharkhand. Correlation and regression methods were used to estimate the impacts of weather on rice yield. Study indicated that temperature, rainfall and sunshine hours have significant effect on the rice yield. Average minimum temperature during sowing to vegetative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Therefore, optimum dose of fertilizer was applied at the rate of 25 kg N, 15 kg P and 15 kg K + ha -1 in three splits at 37, 45 and 57 DAP. Primary atmospheric variables that impact on crop growth and grain production are solar radiation, air temperature, humidity, and precipitation (Kumari et al, 2017). During the season, maximum and minimum temperature ranged between 31.3 to 44.5 ºC and 23.0 to 27.3 ºC and solar radiation ranged between 7.6 to 25.8 MJ m -2 day -1 respectively (Fig 1).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, optimum dose of fertilizer was applied at the rate of 25 kg N, 15 kg P and 15 kg K + ha -1 in three splits at 37, 45 and 57 DAP. Primary atmospheric variables that impact on crop growth and grain production are solar radiation, air temperature, humidity, and precipitation (Kumari et al, 2017). During the season, maximum and minimum temperature ranged between 31.3 to 44.5 ºC and 23.0 to 27.3 ºC and solar radiation ranged between 7.6 to 25.8 MJ m -2 day -1 respectively (Fig 1).…”
Section: Resultsmentioning
confidence: 99%
“…Impact of primary atmospheric variables on crop growth, development and grain production were rainfall, solar radiation, air temperatures, humidity, and precipitation. Reported by Kumari et al (2017). Figure 1 showed that weather conditions had no visible variations.…”
Section: Weather Condition Analysismentioning
confidence: 96%
“…The seed density required for direct seeding should be determined not only by field conditions but also by cultural practices. Field conditions may include water movement as affected by wind speed and soil physical surface conditions (Pragyan Kumari et al, 2017). The density required in the continuous flooding of water seeding might be greater than that required delayed flooding (Yamuchi, 2017).…”
Section: Yield Attributes and Grain Yieldmentioning
confidence: 99%